Occurrence of zoonotic Cryptosporidium and Giardia duodenalis species/genotypes in urban rodents - Tan, Tiong Kai; Low, Van Lun; Ng, Wern Hann; Ibrahim, Jamaiah; Wang, Daryi; Tan, Chun Hoong; Chellappan, Selvi; Lim, Yvonne Ai Lian (Elsevier, 2019)
This report describes the detection of zoonotic Cryptosporidium muris, C. parvum subgenotype IIa and Giardia duodenalis genotype B in urban rodents in Malaysia. A rare occurrence of C. meleagridis was also reported suggesting a role of rodents in mechanical transmission of this pathogen. Utilization of DNA sequencing and subtyping analysis confirmed the presence of zoonotic C. parvum subtypes IIaA17G2R1 and IIaA16G3R1 for the first time in rodents.